Hardness of Flowable Resin Composite from Rice Husk / Nazrul M. Yusoff ...[et al.] - M. Yusoff, Nazrul; Johari, Yanti; Ab Rahman, Ismail; Mohamad, Dasmawati; Khamis, Mohd Fadhli; Husein, Adam; Ariffin, Zaihan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The aim of this study was to evaluate the hardness of two experimental dental flowable resin composites (FRCs) from rice husk in comparison to other commercial flowable resin composites. The nanohybrid silica used as the filler for the experimental FRCs was extracted from rice husk. Two commercial FRCs namely Filtek Z350 flow and Tetric N flow and the experimental FRCs with different loading of Bis-GMA at 50 % (EC50B) and 40 % (EC40B) were used. Ten cylindrical specimens (5 x 2mm) for each material were prepared in acrylic mould, light cured and polished. Prior to hardness test, all the composites were immersed in distilled water at 37 ℃ for 24 h. The Vickers’ hardness number (VHN) was measured using Vickers’ hardness tester and their surface morphology was investigated using scanning electron microscopy (SEM). The data was analyzed by one way ANOVA followed by Dunnett T3 post hoc test. Results showed that Filtek Z350 flow was statistically significantly higher in regards to VHN compared to the other FRCs tested. There was no statistically significant difference in VHN between the Tetric N flow and the two experimental FRCs. SEM showed a well distributed embedded spherical filler particle in all FRCs. In conclusion, the two experimental FRCs were comparable to Tetric N flow however Filtek Z350 flow exhibited the highest hardness. This was possibly attributed to different filler loading. Between the experimental composites, EC40B had a higher hardness which can be explained by dilution effect on monomer system. In general, mechanical properties improved with increased filler loading and dilution of base monomer.